TANGGUNG JAWAB LION AIR GROUP TERHADAP PRAKTIK DISKRIMINASI PENJUALAN KAPASITAS KARGO BERDASARKAN HUKUM PERSAINGAN USAHA(Studi Perkara Terhadap Putusan Komisi Pengawas Persaingan Usaha Nomor 07/KPPU-I/2020) - Ayu Diah Rahmani, (2023)
Based on the Decision on Case Number 07/KPPU-I/2020, KPPU decided that Lion Group Airlines had carried out discriminatory practices related to Cargo Capacity Sales Cooperation. The purpose of this research is to find out the discriminatory practices carried out by Lion Group and the forms of responsibility that must be carried out by Lion Air Group as well as efforts to prevent discriminatory practices from recurring. This study uses normative legal research methods with statutory and case approaches. KPPU, based on its initiative, conducted an investigation into the reported parties as a result of indications of unfair business competition occurring that did not work according to the law. Based on the results of evidence, PT. Lion Mentari, PT. Batik Air Indonesia, and PT. Lion Express is proven to have violated the provisions of Article 19 letter d of Law No. 5 of 1999 concerning the prohibition of discriminatory practices. In the future, it is hoped that all business actors in Indonesia can register their business activities in the Business Competition Compliance Program as regulated in KPPU Regulation No. 1 of 2022. This program provides convenience to KPPU so that it can move more freely in carrying out its supervisory function and prevent business competition violations from occurring. In addition, this program will give a good image and name to actors and their business activities in Indonesia.